2020
DOI: 10.1136/rapm-2020-101396
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of infiltration between the popliteal artery and capsule of the knee (iPACK) block added to local infiltration analgesia and continuous adductor canal block after total knee arthroplasty: a randomized clinical trial

Abstract: BackgroundA combination of motor-sparing analgesia with local infiltration analgesia (LIA) and continuous adductor canal block (CACB) may improve postoperative pain and functional recovery for total knee arthroplasty (TKA). We hypothesized that the addition of a novel technique for posterior knee block, known as the infiltration between the popliteal artery and capsule of the knee (iPACK) block, to LIA with CACB would reduce opioid requirements.MethodsIn this double-blinded randomized controlled trial, 72 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(89 citation statements)
references
References 28 publications
0
87
0
Order By: Relevance
“…The search strategy identified 2180 unique citations. After independent and duplicate screening by two authors (RSD and BL), eight RCTs 13,[25][26][27][28][29][30][31] were identified that fulfilled eligibility criteria. Collectively, these eight RCTs consisted of 777 patients (377 patients received the iPACK block; 400 patients in the control cohort received another modality of peripheral nerve blockade or PAI for knee analgesia).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search strategy identified 2180 unique citations. After independent and duplicate screening by two authors (RSD and BL), eight RCTs 13,[25][26][27][28][29][30][31] were identified that fulfilled eligibility criteria. Collectively, these eight RCTs consisted of 777 patients (377 patients received the iPACK block; 400 patients in the control cohort received another modality of peripheral nerve blockade or PAI for knee analgesia).…”
Section: Search Resultsmentioning
confidence: 99%
“…Bias assessment for all included studies is summarized in Figure 2. All eight RCTs 13,[25][26][27][28][29][30][31] generally demonstrated a low risk of bias in random sequence generation and allocation concealment, blinding of outcome assessment, incomplete outcome data, and selective reporting. In terms of blinding of participants, some RCTs 13,25,26 displayed a high risk for bias because although they blinded all surgeons, recovery room and floor nurses, research assistants, statisticians, and patients, it was impossible to blind the anesthesiologist performing the ultrasound-guided iPACK block who may have participated in the study.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 98%
See 3 more Smart Citations